Retinol-binding protein 4 in skeletal and cardiac muscle: molecular mechanisms, clinical implications, and future perspectives - Zhang, Kangzhen; Wang, Lijuan; Gao, Wei; Guo, Rong (Frontiers in Cell and Developmental Biology, 2025)
Retinol-binding protein 4 (RBP4) has emerged as a critical adipokine involved in the pathophysiology of metabolic and cardiovascular diseases. Beyond its classical role in retinol transport, RBP4 influences insulin resistance, inflammation, lipid metabolism, mitochondrial function, and cellular apoptosis in both skeletal and cardiac muscles. Elevated levels of RBP4 are associated with obesity, type 2 mellitus diabetes, and cardiovascular diseases, making it a potential biomarker and therapeutic target. This comprehensive review elucidates the molecular mechanisms by which RBP4 affects skeletal and cardiac muscle physiology. We discuss its clinical implications as a biomarker for disease risk and progression, explore therapeutic strategies targeting RBP4, and highlight future research directions. Understanding the multifaceted roles of RBP4 could pave the way for novel interventions against metabolic and cardiovascular disorders.